"The zipper effect": Exploring the interrelationship of mental toughness and self-compassion among Canadian elite women athletes. (January 2019) - Wilson, Danielle; Bennett, Erica V.; Mosewich, Amber D.; Faulkner, Guy E.; Crocker, Peter R.E.
Abstract: Objectives: The purpose of this study was to explore how elite women athletes perceived and experienced mental toughness and self-compassion and their compatibility in the pursuit of athletic success and stress management. Method: Adopting an interpretivist constructionist approach, we conducted two semi-structured interviews with seven participants (14 interviews), aged 22 to 34. Through a thematic analysis, we identified and analyzed patterns within the data related to how the athletes experienced and perceived self-compassion and mental toughness. Results: Three overarching themes were identified, including the role of mental toughness as critical for coping with sport-related adversity, the role of self-compassion as critical for coping with sport-related adversity, and self-compassion and mental toughness as compatible. Participants experienced mental toughness as a coping resource, which included perseverance through adversity, remaining present, maintaining perspective, and adequate competition preparation. They perceived that common humanity, mindfulness, and self-kindness were also key to coping with sport-related adversity. Finally, the women identified self-compassion and mental toughness as compatible and contextual processes. Self-compassion was critical to the development of mental toughness, and mindfulness was key to developing and maintaining both self-compassion and mental toughness. Conclusions: The findings revealed that self-compassion and mindfulness are worthy of investigation in elite women athletes, particularly with regards to their utility in coping with sport-related adversity and in achieving a mentally tough mindset. Self-compassion and mental toughness are compatible processes that may both require mindfulness, and if used in an effective and complementary balance could create optimal mindsets for the pursuit of athletic success. Highlights: Adversity was highly prevalent throughout the women's athletic careers. Mental toughness was critical for coping with sport-related adversity. Mental toughness encompassed perseverance, presence, perspective, and preparation. Self-compassion was critical when facing adversity and to achieve mental toughness. Self-compassion and mental toughness were compatible, and both required mindfulness.